Development of a Sustainability Index at the Local Level: methodological proposal and its application in the case study of Rio de Janeiro, Brazil - Ana Luiza Mendes Silva; Matheus Ferreira de Barros; Luan Santos (Production)
Abstract Paper aims This paper presents the methodological development of a sustainability indicator focused on the local level, based on the Municipal Human Development Index (MHDI). Originality The proposed indicator (MHDI+S) was built on the use of an indicator with simple methodology based on information provided by reliable Brazilian research institutes, making it easier to be updated and reproduced in other regions and states. Research method By adding the environmental factor to this well-known index, the proposed indicator (MHDI+S) is then applied to the state of Rio de Janeiro, Brazil, so that the municipalities have been categorized into different clusters. Main findings The results of this categorization were validated by statistical assessment (cluster analysis) showing that the groups have internal homogeneity and external heterogeneity. Implications for theory and practice The proposed indicator (MHDI+S) can assist public management at the local level, decentralizing the well-established federal perspective,